Preconcentration and Determination of Chlorophenols in Wastewater with Dispersive Liquid–Liquid Microextraction Using Hydrophobic Deep Eutectic Solvents. (22nd January 2020) - An, Yena; Ma, Wanwan; Row, Kyung Ho
Abstract: Hydrophobic deep eutectic solvents (DESs) were synthesized and developed for the preconcentration of three chlorophenols from wastewater by dispersive liquid–liquid microextraction (DLLME). The analyte concentrations were determined by high-performance liquid chromatography (HPLC). The hydrophobic DESs were prepared with the combination of hydrogen bond donors of decanoic acid or octanoic acid with different hydrogen bond acceptors of quaternary ammonium salts of tetrabutylammonium chloride, tetraoctylammonium chloride, methyltrioctylammonium chloride, and tetraheptylammonium chloride). Following the study of the stability and characterization by Fourier transform infrared spectroscopy, the hydrophobic DESs were developed as extractants and employed for the removal of 4-chlorophenol (4-CP), 2, 4-dichlorophenol (2, 4-DCP), and 2, 4, 6-trichlorophenol (2, 4, 6-TCP) from wastewater. Using hydrophobic DESs as the microextraction solvents, several key parameters were optimized, including the type and volume of the hydrophobic DES, pH, and time of the extraction procedure. Under the optimized conditions, good recoveries from 90.8% to 93.0% were obtained for the three chlorophenols. The limits of detection were less than 0.05 µg/mL with relative standard deviations between 1.8% and 3.1%. The method was applied for the isolation and determination of synthetic chlorophenols in wastewater.